Racial differences in hemoglobin and plasma volume variation: implications for muscle performance and recovery - Sellami, Maha; Chamari, Karim; Zagatto, Alessandro Moura; Kebsi, Wiem; Chaouachi, Anis; Zouhal, Hassane (Taylor & Francis, 2017)
Objective: To examine the effect of race differences on sprint performance, Hemoglobin (Hb), Hematocrit (Ht) and plasma volume (PV) variation in response to repeated sprint exercise. Design: Thirty-six healthy, moderately trained men and women (20.8 ± 0.2 year-old) volunteered to participate in this study. They were allocated to one of the four groups according to their gender and race: Black men’s group (BM, n = 9), White men’s group (WM, n = 9), Black women’s group (BW, n = 9) and White women’s group (WW, n = 9). All participants performed the running-based anaerobic sprint test (RAST), which consists of six 35-m sprints with 10 s of recovery in-between. Six venous blood samples were collected to determine Hb, Ht and PV levels at rest, after warm-up, immediately post- and at 5, 15 and 30 min post-RAST. Blood lactate is also sampled during the 3rd minutes of recovery. Results: The best running time was significantly shorter (P = .002) in BW compared to WW. We have observed significantly higher Hb (P = .010) and Ht (P = .004) levels in BW compared to WW during the 5th minute of recovery. During RAST, the PV decreased significantly (P = .007) in WM only. Black groups had lower (P < .05) lactate levels compared to the white subjects. During recovery, PV increase was significantly (P = .003) higher in WW compared to BW during the 5th minute of recovery. Conclusion: This study demonstrated that sprint and repeated sprint performances were different between white and black women. Differences in anaerobic performance between the groups were associated with racial differences in lactate levels and blood count among women’s group during recovery time. Hence, it is important to take into account this race-related difference in hematological parameters in responses to intense efforts.
Keywords: aerobic capacity; blood volume; dehydration; Ethnicity; repeated intense efforts